2009
DOI: 10.1111/j.1745-4514.2009.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants- And Oxidants-Resistant Alkaline Proteases From Common Carp (Cyprinus Carpio L) Processing Waste

Abstract: Intestine from Cyprinus carpio L., an important fish in the Brazilian Aquaculture, is proposed in this work as a source of alkaline protease. The intestine crude extract was submitted to a partial purification by ethanol precipitation. The fraction 30–70% (v/v) of ethanol concentration showed higher recovery and specific activity when compared with the crude extract and was submitted to further studies. The optimal temperature and pH were found to be 50C and 11.0, respectively. The enzymatic activity was activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
7
9
0
Order By: Relevance
“…It can also be reported that the crude alkaline protease is more stable at 30 • C than 40 • C. These finding were similar to those for striped seabream (L. mormyrus; El-Hadj Ali et al, 2011), tambaqui proteases (C. macropomum; Espósito et al, 2009b), and Nile tilapia (O. niloticus; Mendes et al, 2009).…”
Section: Stability Of the Alkaline Crude Enzyme Extract With Commercisupporting
confidence: 78%
“…It can also be reported that the crude alkaline protease is more stable at 30 • C than 40 • C. These finding were similar to those for striped seabream (L. mormyrus; El-Hadj Ali et al, 2011), tambaqui proteases (C. macropomum; Espósito et al, 2009b), and Nile tilapia (O. niloticus; Mendes et al, 2009).…”
Section: Stability Of the Alkaline Crude Enzyme Extract With Commercisupporting
confidence: 78%
“…The relative activities at 40 and 60°C were about 76% and 37.5%, respectively, of that at 50°C. The optimal temperature of L. mormyrus proteases was similar to that of common carp (Cyprinus carpio L.) [34] and lower than that of Nile tilapia and tambaqui proteases [23,35] which have optimal temperatures in the range of 55 and 60°C, respectively. The thermal stability profile showed that alkaline enzyme extract is fully active for at least 60 min at 30 and 40°C, which is desirable for laundry purposes and from the ecological and economical point of view, mainly, because of saving of energy.…”
Section: Effect Of Temperature On the Activity And Stability Of The Vmentioning
confidence: 84%
“…The visceral protease activity pattern was similar to those of other fish species such as intestine proteases of Nile tilapia (Oreochromis niloticus), proteases from the intestine and pyloric caeca of crevalle jack (Caranx hippos), spotted goatfish (Pseudopeneus maculates), parrotfish (Sparisoma sp. ), and traira (Hoplias malabaricus) [33], although, alkaline proteases from tambaqui (Colossoma macropomum) and common carp (Cyprinus carpio) intestine were reported to be active at higher pH values (10.0-12.0) [23,34].…”
Section: Effect Of Ph On Activity and Stability Of Alkaline Enzyme Exmentioning
confidence: 99%
“…The relative activities at 40 and 60 1C were about 59% and 40.1%, respectively, of that at 50 1C. The optimal temperature of S. scriba proteases was lower than that of farmed giant catfish, which exhibited optimal temperature at 60 1C (Vannabun et al, 2014) and similar to crude enzyme extracted from Lithognathus mormyrus (El Hadj-Ali et al, 2011) and Cyprinus carpio L. (Esposito et al, 2009). The thermal stability profile, reported in Fig.…”
Section: Effect Of Ph On Activity and Stability Of Alkaline Enzyme Exmentioning
confidence: 88%